Towards a Penal Law for Religious? (II/2) Consecrated Life in the Light of Pope Francis’s 2021 Reform of Book VI of the CIC: Part II. Special Considerations (2): the Evangelical Counsel of Chastity as the Object of Penal Protection - Skonieczny, Piotr (Prawo Kanoniczne, 2025)
The author analyses the discipline of religious life from the perspective of penal law in the light of Pope Francis’s recent reform of Book VI CIC/21 of 2021. The author asks whether it is possible to speak of a penal law for religious after the reform of Book VI of 2021. The third article addresses specific issues, particularly the penal protection of the evangelical counsel of chastity. First, the author analyses the substantive scope — the references used by the legislator in new canon 1398 §2 CIC/21 — and criticises the narrowing of this delict’s scope. He then points out that the new delict of consecrated persons, referred to in can. 1398, § 2 CIC/21, is not reserved for the Dicastery for the Doctrine of the Faith (II.1). This has serious legal consequences, particularly with regard to the criminal statute of limitations (II.2) and the error aetatis, for which see art. 6, n. 1, pars secunda SST/21 (II.3). From the victim’s perspective, the differentiated liability of the perpetrator for the same criminal acts is considered inconsistent and unjust. Finally, the author criticises canon 1394 §2 CIC/21, which has not been adapted to new social phenomena, such as homosexual or pluriamorous unions, including those entered into by consecrated persons (III.). Despite these criticisms, the author believes that the reform of Book VI of the CIC/21 introduces important changes to the penal protection of the evangelical counsel of chastity. The previous proper delict prohibiting religious from marrying (can. 1394, § 2 CIC/21) and the new proper delict contra VI of consecrated persons (can. 1398, § 2 CIC/21) form a starting point for the penal law for consecrated persons. The author examines the transition from the model present in the 1983 Code — whereby chastity was mainly protected by the laws of Institutes of Consecrated Life — to the concept of universal protection of this counsel introduced by the 2021 reform (‘Conclusioni parziali II’: Partial conclusions II).